Oliver twist - "Dickens, Charles" (Puffin London, 2017)
After Oliver Twist asks for more food, he has to flee the workhouse for the streets of London. Here he meets the Aftful Dodger, who leads him to Fagin and his gang of pickpockets. When a thieving mission goes wrong, Oliver narrowly avoids prison and finds himself in the care of kind Mr Brownlow. But Fagin and the brutal Bill Sikes go in search of the young orphan, determined to drag him back ... [from back cover]